Electrolysis Free Micro EDM in Water Using Electrostatic Induction Feeding Method - Tomohiro KOYANO; Masanori KUNIEDA (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2012)
This paper describes the machining characteristics of electrolysis-free micro EDM in water using the electrostatic induction feeding method. With the electrostatic induction feeding method, if deionized water is used for the working liquid, electrolysis can be prevented because bipolar voltage is applied to the working gap. Results of micro-holes drilling showed that the material removal rate with deionized water is higher than that with oil, and the oversize of holes machined in deionized water is smaller. Moreover, micro-holes could be drilled successfully even in a tap water with the oversize of several micrometers using this method.